إستخدامات المرأة العراقیة للقنوات الفضائیة دراسة میدانیة (Journal of the College of Education for Women, 2019)
This study aims to know how much and how long the Iraqi women'swatch space channels and expose to them and if these channels mee theirneed to get knowledge information an entertainment . the role played bythese channels to provide Iraqi women with news about their community tomeet their needs and motives. this study also aims to know much the Iraqiwomen expose to these channels and to know the favorable type of thechannels for them and the causes of that and know favorable programs andwhy. also it aims to know the types of the if these channels deal with the Iraqiwomen's problems and if the women get any advantage either behaviorknowledge for the watching these channels .